Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14020331
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Tumor Markers for Advanced Thymic Carcinoma: A Retrospective Analysis from the NEJ023 Study

Abstract: The optimal tumor marker for predicting the prognosis of advanced thymic carcinoma (ATC) remains unclear. We conducted a multi-institutional retrospective study of patients with ATC. A total of 286 patients were treated with chemotherapy. Clinicopathological information, including serum tumor markers, was evaluated to determine the overall survival (OS) and progression-free survival (PFS). The carcinoembryonic antigen, cytokeratin-19 fragment, squamous cell carcinoma (SCC) antigen, progastrin-releasing peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The main clinico-pathological prognostic factors for TETs are tumor size, spread, resection status, histological type, patient characteristics (age and comorbidities), and treatment response [ 43 , 51 , 52 , 53 ]. In addition, few studies have reported the prognostic value of serum biomarkers, in particular lactate dehydrogenase and NSE, neutrophil-to-lymphocyte ratio, and immunohistochemical stainings, such as bcl-2, ki-67, MMP-2, p21, and TIMP-2 [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Staging Systemsmentioning
confidence: 99%
“…The main clinico-pathological prognostic factors for TETs are tumor size, spread, resection status, histological type, patient characteristics (age and comorbidities), and treatment response [ 43 , 51 , 52 , 53 ]. In addition, few studies have reported the prognostic value of serum biomarkers, in particular lactate dehydrogenase and NSE, neutrophil-to-lymphocyte ratio, and immunohistochemical stainings, such as bcl-2, ki-67, MMP-2, p21, and TIMP-2 [ 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Staging Systemsmentioning
confidence: 99%